KONTRIBUSI STATUS GIZI DAN KEMAMPUAN MOTORIK TERHADAP KESEGARAN JASMANI PADA SISWA KELAS 4 DI SEKOLAH SD NEGERI 06 BELUTU KECAMATAN KANDIS - Purwanto, Purwanto; Wijayanti, Ni Putu Nita; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this research is that students are less active in doing Physical Education learning movements, the movements that are performed are usually passive, this is because the diet in children is usually difficult for children to eat or do not want to eat at all if they want to go to school. The aim of this research was to determine the contribution of nutritional status and motor skills to the physical fitness of grade 4 students of SD Negeri 06 Belutu. The population in this research consisted of group 4 students, which equates to 30 people. The sampling technique was targeted sampling. Based on the correlation test to determine the relationship between the variables studied, the first hypothesis of the performed statistical analysis obtained r count of 0.852 and r table of 0.575, so r count> r table. This means that there is a link between nutritional status and physical fitness and that it contributes 72.59%. In the second hypothesis it is obtained that r count is 0.653 and r table is 0.575, so r count <r table there is a relationship between motor skills and physical fitness and contributes 42.63%. In the third hypothesis of the performed statistical analysis, it is obtained that the R count is 0.994 and the r table at the level of α = 0.05 is 0.575, so r count> r table. This means that there is a link between nutritional status and motor skills together on physical fitness and it contributes 98.80%.Key Words: Nutritional Status, Motor Skills, Physical Fitness